Effect of different C/N ratios of biofloc technology in the growth of Pacific white shrimp (Litopenaeus vannamei) juvenile production, quantity of floc, and total ammonia nitrogen (TAN) level of the culture system - Figueroa, Jerian Dale Verdejo
This study evaluated the effect of different C/N ratios of the BFT culture system on the growth of juvenile L. vannamei, quantity of produced floc, and in the ammonia level of the culture medium. Triplicate set-ups of culture systems were utilized and maintained at varying C/N ratios (8, 12, 16). Control (C/N 0) set-ups were established by the absence of molasses. 40 juvenile shrimps were stocked per tank with a water holding capacity of 80 L. Different amount of molasses was added at a daily basis to maintain the experimental treatments and to assess its effects. At the end of experiment, results showed that maintaining the C/N ratio at different levels does not cause a significant difference (p > 0.05) in the growth parameters of L. vannamei. In terms of ammonia reduction, C/N 16 yielded the lowest ammonia value with 0.36(±0.255) ppm at the final week. The density of biofloc is also affected with the change in C/N ratio. C/N 0 and 16 produced the highest level with 10.5±2 and 11.5±1.8 respectively. The overall results suggest that C/N ratio tends to affect the environmental conditions of the culture system; however, it may not have a direct effect on the growth of L. vannamei.